HUBUNGAN PENGETAHUAN PASIEN TENTANG PERAWATAN PASCA OPERASI KATARAK DENGAN MOTIVASI UNTUK KONTROL KE RUMAH SAKIT MATA BALI MANDARA PROVINSI BALI TAHUN 2016 - Wijaya, I Nyoman Purna; Dewi, Ayu Puja Astuti; Kamaryati, Ni Putu (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2017)
Cataracts are cloudiness in the lens of eyes that can only be cured by surgical procedure. The high number of patients with cataract surgery does not matched with their understanding on how the treatment and management of post operative cataract patient adherence to exercise control over. The purpose of this study is to determine the relationship of patients knowledge about post operative treatment of cataract with the motivation to see the doctor as outpatient at Bali Mandara Eye Hospital in 2016.This study used a descriptive correlation design with cross sectional approach. The sampling used consecutive sampling with a total sample of 88 respondents. The data was collected by using questionnaires. The data were analysed using univariate and bivariate technique with SPSS 20.0 program.Most of the patients knowledge about post operative treatment of cataract in good categories 73.9% (65 respondents) and motivation to do outpatient consultation at Bali Mandara Eye Hospital is categorized high, which is 98.9% (87 respondents). Pearson Product Moment analysis results showed p-value <0.001 and r = 0.634, which mean there is a connection between patients knowledge about post operative treatment of cataract with the motivation to do outpatient consultation at Bali Mandara Eye Hospital in 2016.A Good knowledge on post operative treatment of cataract, is expected to motivate patients to actively visit the hospital for outpatient consultation so that complications after cataract surgery can be prevented Keywords: knowledge, motivation, post-operative treatment of cataract